Assessment of Pain Anxiety, Pain Catastrophizing, and Fear of Pain in Children and Adolescents With Chronic Pain: A Systematic Review and Meta-Analysis. (25th July 2017) - Fisher, Emma; Heathcote, Lauren C; Eccleston, Christopher; Simons, Laura E; Palermo, Tonya M
Abstract: Objective: To conduct a systematic review of pain anxiety, pain catastrophizing, and fear of pain measures psychometrically established in youth with chronic pain. The review addresses three specific aims: (1) to identify measures used in youth with chronic pain, summarizing their content, psychometric properties, and use; (2) to use evidence-based assessment criteria to rate each measure according to the Society of Pediatric Psychology (SPP) guidelines; (3) to pool data across studies for meta-analysis of shared variance in psychometric performance in relation to the primary outcomes of pain intensity, disability, generalized anxiety, and depression. Methods: We searched Medline, Embase, PsycINFO, and relevant literature for possible studies to include. We identified measures studied in youth with chronic pain that assessed pain anxiety, pain catastrophizing, or fear of pain and extracted the item-level content. Study and participant characteristics, and correlation data were extracted for summary and meta-analysis, and measures were rated using the SPP evidence-based assessment criteria. Results: Fifty-four studies (84 papers) met the inclusion criteria, including seven relevant measures: one assessed pain anxiety, three pain catastrophizing, and three fear of pain. Overall, five measures were rated as "well established." We conducted meta-analyses on four measures with available data. We found significant positive correlations with the variables pain intensity, disability, generalized anxiety, and depression. Conclusion: Seven measures are available to assess pain anxiety, pain catastrophizing, and fear of pain in young people with chronic pain, and most are well established. We present implications for practice and directions for future research.